TYPES OF DICTIONARIES: STANDARDS, NORMS AND PROBLEMS OF COMPLYING TERMINOLOGICAL DICTIONARIES - Abdiyeva Xumora Gulzor qizi Navoi State Pedagogical Institute, Faculty of English language; literature, 2nd stage master’s degree Qayumova Munavvar Sanoqulovna associate professor (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article provides feedback on the concept of a dictionary, dictionaries a dictionary it’s types, description and classification. Key words: word, lexeme, dictionary, definition,lexicography ,technical words,collocations, study dictionary , classification, lexical- grammatical